2013
DOI: 10.2188/jea.je20130048
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among Japanese With a History of Kawasaki Disease: Results at the End of 2009

Abstract: BackgroundThe long-term outcomes of Kawasaki disease (KD) are unknown.MethodsFifty-two collaborating hospitals collected data on all patients who had received a new definite diagnosis of KD between July 1982 and December 1992. Patients were followed until December 31, 2009 or death. Standardized mortality ratios (SMRs) were calculated based on Japanese vital statistics data.ResultsOf the 6576 patients enrolled, 46 (35 males and 11 females) died (SMR: 1.00; 95% CI: 0.73–1.34). Among persons without cardiac sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 29 publications
1
31
0
1
Order By: Relevance
“…51 A more recent study from Japan showed that the SMR beyond the acute illness was elevated for all patients with cardiac sequelae (SMR, 1.86; 95% confidence interval, 1.02-3.13), thus, stressing the importance of long-term surveillance for this subgroup of patients. 52 Patients without cardiac sequelae after the acute phase had a lower mortality relative to the general population (SMR, 0.65; 95% confidence interval, 0.41-0.96). In the continental United States, using administrative data that could include readmissions for coronary disease, the in-hospital mortality rate is ≈0.17%.…”
Section: Applying Classification Of Recommendations and Level Of Evmentioning
confidence: 95%
“…51 A more recent study from Japan showed that the SMR beyond the acute illness was elevated for all patients with cardiac sequelae (SMR, 1.86; 95% confidence interval, 1.02-3.13), thus, stressing the importance of long-term surveillance for this subgroup of patients. 52 Patients without cardiac sequelae after the acute phase had a lower mortality relative to the general population (SMR, 0.65; 95% confidence interval, 0.41-0.96). In the continental United States, using administrative data that could include readmissions for coronary disease, the in-hospital mortality rate is ≈0.17%.…”
Section: Applying Classification Of Recommendations and Level Of Evmentioning
confidence: 95%
“…The most frequent cause of death was KD-related cardiovascular sequelae (13 subjects, 0.2%) followed by malignancy (7 subjects, 0.1%), trauma (7 subjects, 0.1%), and suicide (7 subjects, 0.1%). There were 1,003 subjects with cardiac sequelae of KD in this cohort and seven (0.6%) died of suspected or confirmed cardiovascular causes over the 27-year period of the study [16]. Only the mortality rate among Japanese with cardiac sequelae due to KD was significantly higher than that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…CAA may remain silent after KD until adulthood when myocardial ischemia can lead to sudden death [615]. In children in whom the disease is diagnosed and treated, the death rate is less than one per hundred and autopsies are rare [16]. Although suspected KD cases have been reported in the forensic literature, there has been no systematic study to determine the incidence of such cases [8].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, data both supporting and not supporting the progression, exist . Follow‐up epidemiologic observation would provide meaningful data on the question . If KD vasculitis promotes the development of atherosclerosis, this has implications for circulatory disease in general, because so many people have the risk factor, as shown in this study.…”
Section: Discussionmentioning
confidence: 76%